REVITALISASI PENDIDIKAN KEAGAMAAN ISLAM DI MANDAILING NATAL - Asrin, Ahmad (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2019)
The command to teach prayer is actually a philosophy that is very meaningful, because it is from prayer that all goodness starts. The punch in question is tarbiyah (education), not a blow that is dangerous because ofemotional. Considering the importance of strengthening the foundations of Islamic creed and mental formation of morality for children, on the other hand the enormous challenges of the effects of globalization of technology and information are very massive, so there is no other choice that the revitalization of religious education must be echoed. This calls for the participation of all education holders, especially the local government and non-formal figures in the community because without the support of all lines, the big goal could not be realized. Mandailing Christmas is not only enough to have the jargon of the City of Santri, the foyer of the mecca of Sumatra etc. without making anticipatory efforts of the dangers of Drugs etc. that are in sight.